'Sacrifice zone': The environment–territory–place of disposable lives. (14th October 2020) - de Souza, Marcelo Lopes
Abstract: 'Sacrifice zone' is how a certain type of segregated and stigmatized space has become internationally known. In such a space, the physical and mental health and the quality of life of human beings are compromised in the name of 'economic development' or 'progress' – but ultimately for the sake of capitalist interests. This article offers a discussion of how environmental issues, power relations and the production of subjectivity intersect in the production of a kind of space that is typical of how residential segregation correlates with patterns of industrial location and the neglect of the health and well-being of the poor by the state apparatus in the (semi) periphery of the capitalist world system.